Morphological analysis of interbody fusion following posterior lumbar interbody fusion with cages using computed tomography. Issue 34 (August 2017) - Seo, Dong Kwang; Kim, Myeong Jong; Roh, Sung Woo; Jeon, Sang Ryong
Abstract : Abstract: Posterior lumbar interbody fusion (PLIF) using cages in conjunction with pedicle screw fixation is considered the gold standard for surgical treatment of degenerative lumbar spine disorders due to its biomechanical stability and high fusion rate. However, research regarding patterns of fusion in the interbody space during the early postoperative period is lacking. Sixty consecutive patients were recruited from May 2013 to June 2015. All patients underwent PLIF using 2 titanium cages filled with local bone chips from decompressed lamina and facet bone in conjunction with pedicle screw fixation. Computed tomography scans were obtained 3 to 6 months following surgery in order to evaluate the partial fusion state. Computed tomography (CT) classification of fusion morphology was divided into 8 groups and then into compartments according to fusion space, and the rate of fusion for each was calculated. Further follow-up was conducted to confirm fusion state and assess outcomes. The most frequent pattern of interbody fusion was bilateral intra-cage fusion with unilateral lateral bridging of extra-cage areas (N = 36, 43.4%); the least frequent was interspace bridging of the 2 cages alone (N = 0, 0%). The fusion rate for the intra-cage area (Compartment 1) reached 100%. However, the fusion in the lateral space outside of cages (Compartment 2) was not satisfactory, though reasonable (72.3%). All patients were confirmed as achieving adequate fusion at the final follow-up, with improved clinical outcomes. Widening of the contact area between the vertebral body and cages is recommended to promote increased interbody fusion during the early postoperative period.